2024
DOI: 10.3390/plants13020153
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Therapeutic Potential of Vaccinium Berries in Breast Cancer—A Review

Naser A. Alsharairi

Abstract: Breast cancer (BC) is the largest contributor to cancer deaths in women worldwide. Various parts of plants, including fruits, are known for their therapeutic properties and are used in traditional medicine. Fruit species exhibit anticancer activities due to the presence of bioactive natural compounds such as flavonoids and carotenoids. The Vaccinium spp. are fleshy berry-like drupes and are rich in bioactive compounds, with flavonols, flavanols, chalcones, and phenolic acids as the major groups of compounds. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(96 reference statements)
0
1
0
Order By: Relevance
“…A recent review of experimental studies has demonstrated that Vaccinium bioactives, including ACNs, PACs, gallic acid, and hippuric acid, have therapeutic potential in breast cancer treatment. These bioactives exert antiproliferative, anti-inflammatory, apoptotic, and autophagic activities against breast cancer cells through inhibition and/or activation of molecular genes as potential mechanisms for these effects [32]. Despite a few preclinical studies showing results of cranberry PACs in PCa and OC treatment [33], to date, no review has provided a comprehensive understanding of the role of Vaccinium bioactives in RC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of experimental studies has demonstrated that Vaccinium bioactives, including ACNs, PACs, gallic acid, and hippuric acid, have therapeutic potential in breast cancer treatment. These bioactives exert antiproliferative, anti-inflammatory, apoptotic, and autophagic activities against breast cancer cells through inhibition and/or activation of molecular genes as potential mechanisms for these effects [32]. Despite a few preclinical studies showing results of cranberry PACs in PCa and OC treatment [33], to date, no review has provided a comprehensive understanding of the role of Vaccinium bioactives in RC treatment.…”
Section: Introductionmentioning
confidence: 99%